2011
DOI: 10.1111/j.1537-2995.2011.03435.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of immediate or delayed addition of platelet additive solution on the in vitro quality of apheresis platelets

Abstract: Adding PAS immediately or 2 hours after collection does not result in different in vitro quality of PLTs stored up to 7 days. The good recovery of clotting factors with no signs of activation indicates a good quality of CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…In the same way, Gyöngyössy et al founded that platelet concentrates resuspended in additive solution with glucose showed similar characteristics in activation (CD62P), morphology, pH glucose metabolism and swirl, when they were compared to platelets in plasma [38]. Ringwald et al [39] suggested that adding PAS immediately or 2 hours after the collection does not affect the in vitro activation and quality of stored platelets up to 7 days. Anyway, we observed significant differences in CD62P between platelets in PAS with respect to PAP only at day 5.…”
Section: Discussionmentioning
confidence: 94%
“…In the same way, Gyöngyössy et al founded that platelet concentrates resuspended in additive solution with glucose showed similar characteristics in activation (CD62P), morphology, pH glucose metabolism and swirl, when they were compared to platelets in plasma [38]. Ringwald et al [39] suggested that adding PAS immediately or 2 hours after the collection does not affect the in vitro activation and quality of stored platelets up to 7 days. Anyway, we observed significant differences in CD62P between platelets in PAS with respect to PAP only at day 5.…”
Section: Discussionmentioning
confidence: 94%
“…Es ist möglich, auch ATK plasmareduziert in additiver Lösung herzustellen [64][65][66][67][68][69] [90]. In diesen Studien wurden fast ausschließlich ATK verwendet [83,87,95].…”
Section: Hb-gehalt Der Ekunclassified
“…Even within recent publications, assessment of CD62P expression levels at or just past expiry (5-or 6-day stored) in platelet components produced by the same method (platelet-rich plasma) varies between 15% [9] and 47% [3]. These differences lead to difficulties in collating results from multicentre studies [10,11] and further hamper efforts to determine the clinical relevance of CD62P expression and to further develop CD62P measurement as a meaningful assessment of platelet quality. This issue was first investigated by the Biomedical Excellence for Safer Transfusion (BEST) Collaborative more than a decade ago.…”
Section: Introductionmentioning
confidence: 99%